Cognitive Warfare and AI-Driven Disinformation: Implications for Decision-Making in Hybrid Conflict Scenarios - Marsili, M. (X Media International Scientific Conference of the series “Decisions in situations of endangerment”, 2025)
In today’s security environment, characterized by hybrid threats and non-linear warfare, decision-makers increasingly face adversarial manipulation of information ecosystems. AI-driven cognitive warfare—leveraging tools such as deepfakes, large language models, and immersive synthetic environments—poses a substantial risk to rational decision-making, operational integrity, and societal resilience. These strategies aim to erode trust, exploit cognitive biases, and shape adversarial behaviors without direct kinetic engagement. This study examines the use of artificial intelligence in hostile information operations and the implications for military, political, and crisis-related decision-making under uncertainty. Drawing on case studies from the Russo-Ukrainian conflict and recent NATO research, the analysis highlights the psychological, ethical, and operational vulnerabilities exposed by AI-enabled disinformation campaigns. The paper proposes a strategic framework for resilience and suggests proactive mitigation strategies, including advanced training, counter-AI tools, and a multi-domain doctrine for information defense. The contribution argues that safeguarding cognitive sovereignty is critical to maintaining command effectiveness and national security in future conflict scenarios.